Neuroplasticity and Successful Cognitive Aging: A Brief Overview for Nursing - Vance, David E. (2012)
The brain remains dynamic even in older age and can benefit from mental exercise. Thus, it is important to understand the concepts of positive neuroplasticity and negative neuroplasticity and how these mechanisms either support or detract from cognitive reserve. This article provides a brief review of these key concepts using four exemplary studies that clearly demonstrate the effects these neurological mechanisms exert on cognitive reserve and cognitive functioning. From this review, a working knowledge of how neuroplasticity and cognitive reserve are expressed in patients will be provided along with how this information can be incorporated into nursing practice and research.